1982
DOI: 10.1042/bj2010395
|View full text |Cite
|
Sign up to set email alerts
|

The exclusion of human serum albumin by human dermal collagenous fibres and within human dermis.

Abstract: Preparations of dermal collagenous fibres and slices of human dermis have been equilibrated with 125I-labelled monomeric human serum albumin. The space inaccessible to the albumin in the fibres and in the dermis was determined by subtraction of the accessible space, calculated from the radioactivity of the specimen, from its total fluid. For a fibre preparation examined in detail, the fluid exclusion was independent of the concentration of either albumin or collagen. Binding of albumin to the fibres was not de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 29 publications
4
29
1
Order By: Relevance
“…Gel electrophoresis of sample B indicated that -10 % of the albumin was in the form of dimers (P. Knox, personal communication). Oligomer contents of 3-34% have been reported in other commercial albumin preparations (Blaabjerg, Hyltoft & Peterson, 1979;Bert, Mathieson & Pearce, 1982). J.…”
Section: Resultsmentioning
confidence: 99%
“…Gel electrophoresis of sample B indicated that -10 % of the albumin was in the form of dimers (P. Knox, personal communication). Oligomer contents of 3-34% have been reported in other commercial albumin preparations (Blaabjerg, Hyltoft & Peterson, 1979;Bert, Mathieson & Pearce, 1982). J.…”
Section: Resultsmentioning
confidence: 99%
“…This network is thought to effectively reduce the distribution volume such that the interstitium acts in a size exclusion manner, excluding very large molecules and thereby promoting their interstitial transport. 19,27,[30][31][32] The process of macromolecular diffusion across the interstitium is likely dictated by molecular size, the presence of diffusional microdomains, and physical and electrostatic interactions with the various components of the interstitium. In this regard, Bell and co-workers suggest that steric effects predominate, 19 however, a clear picture of these complex interactions is still elusive.…”
Section: Physiology Of the Interstitial Spacementioning
confidence: 99%
“…The total concentration of serum proteins in dermis is 11 mg/g, based on the measurements of Bert et al16 in postmortem human dermis. The concentration in the albumin accessible regions (approximately 32% of the fluid fraction)17 has been estimated to be 2.7% (w/v) 7. It is furthermore evident that albumin and other serum proteins can migrate slowly through the tissue; otherwise, they would accumulate in dermis rather than being cleared in the lymph.…”
Section: Introductionmentioning
confidence: 99%